Automatic Control System for Hybrid Electrical Energy Supply Based on Internet of Things - M. Edwin Syah Effendy; RD Kusumanto; Carlos RS (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
The utilization of renewable energy is slowly starting to become one thing that to be interesting inside the development of science technology. The utilization of renewable energy is from at least two renewable energy (Solar Power Plants and Wind Power Plants), State Electricity Enterprise (PLN), and Generator Sources. This device could be operated automatically and integrated on the internet, which has a monitoring system such as voltage, inside which will be used to control everything inside that system. This device is designed to be operated in a combinational manner. This means to be operated based on the voltage value which qualified to activate the load. The utilization of the 3.3V microcontroller is able to design an efficient and low-cost board. Besides that, the device also uses the PLN and Generator set sources as the power backup when the main power runs out. Base on the research noted, this device will distribute the electric source to the houses, which means beneficial for the local society. This device might be applied automatically to four different sources with C++ Programming language to set the point value.